Direct period measurement for fiber Bragg grating using an optical imaging technique - Ali, M.M.; Lim, K.S.; Yang, H.Z.; Chong, W.Y.; Lim, W.S.; Ahmad, Harith (Optical Society of America, 2013)
This paper proposes an approach based on an optical imaging technique for the period measurement of fiber Bragg gratings (FBG). The simple, direct technique involves a differential interface contrast (DIC) microscope and a high-resolution CCD camera. Image processing is performed on the microscope images to obtain low-noise grating profiles and then the grating periods. Adopting a large image sample size in the image processing can reduce uncertainty. During the investigation, FBGs of different grating periods are fabricated by prestraining the photosensitive fibers during the UV-writing process. A good linearity between the measured Bragg wavelengths and grating periods is observed and the measured strain—optics coefficient was found to be in agreement with reported literature.